2010
DOI: 10.33151/ajp.8.3.93
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory Factor Analysis: A Five-Step Guide for Novices

Abstract: Factor analysis is a multivariate statistical approach commonly used in psychology, education, and more recently in the health-related professions. This paper will attempt to provide novice researchers with a simplified approach to undertaking exploratory factor analysis (EFA). As the paramedic body of knowledge continues to grow, indeed into scale and instrument psychometrics, it is timely that an uncomplicated article such as this be offered to the paramedic readership both nationally and internation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
1,486
2
71

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,743 publications
(1,744 citation statements)
references
References 21 publications
12
1,486
2
71
Order By: Relevance
“…Hence, in present study factor analysis was applied in order to reduction of 23 attitudinal items into small number of identified factors with capability of displaying most of the primarily observed variance (Maier, 2007). The Kaiser-Meyer-Olkin (KMO) measure of sampling adequacy of 0.86 and 0.82 for visitors activities and facilities satisfactions respectively, with Bartlett's test of Sphericity significant at the 1% level showed that our data set is suitable to run factor analysis (Hutcheson and Sofroniou, 1999;Williams et al, 2012). Correlation matrix (presented in Appendix 1) with sizable correlations among the variables indicates the suitability of variables to be included in factor analysis.…”
Section: Factor Analysismentioning
confidence: 92%
“…Hence, in present study factor analysis was applied in order to reduction of 23 attitudinal items into small number of identified factors with capability of displaying most of the primarily observed variance (Maier, 2007). The Kaiser-Meyer-Olkin (KMO) measure of sampling adequacy of 0.86 and 0.82 for visitors activities and facilities satisfactions respectively, with Bartlett's test of Sphericity significant at the 1% level showed that our data set is suitable to run factor analysis (Hutcheson and Sofroniou, 1999;Williams et al, 2012). Correlation matrix (presented in Appendix 1) with sizable correlations among the variables indicates the suitability of variables to be included in factor analysis.…”
Section: Factor Analysismentioning
confidence: 92%
“…Multiple criteria were used to determine retention of factors (Williams, Brown, & Onsman, 2010), including eigenvalues >1, a visual analysis of the produced Scree plot, and interpretability of the factor solutions. The Kaiser-Meyer-Oklin (KMO) measure of sample adequacy was assessed (KMO statistic >.80) and Bartlett's Test of Sphericity (p < .05) indicated that the sample was adequate for EFA.…”
Section: Exploratory Factor Analysismentioning
confidence: 99%
“…The Kaiser-Meyer-Oklin (KMO) measure of sample adequacy was assessed (KMO statistic >.80) and Bartlett's Test of Sphericity (p < .05) indicated that the sample was adequate for EFA. The analysis was conducted over a number of iterations and the total variation explained by the factors was set between 50% and 75% (Williams et al, 2010). Tabachnick and Fidell (2001) cite .32 as a good rule of thumb for the minimum loading of an item, which equates to approximately 10% overlapping variance with the other items in that factor.…”
Section: Exploratory Factor Analysismentioning
confidence: 99%
“…A correlation-matrix showed no correlations higher than 0.80 indicating there was no multi-collinearity (Mortelmans and Dehertogh, 2008). Within all the components, factorability was higher than 0.30 and significant at the 0.001-level (Williams et al 2012). The loading of all the items, except two, for each component was above 0.40.…”
Section: Results: Construct Validitymentioning
confidence: 77%